Complete chloroplast genome sequence of Thalictrum viscosum W.T.Wang & S.H.Wang, 1979 (Ranunculaceae). Issue 9 (2nd September 2022) - Cai, Haohong; Shi, Wenbo; Weicai, Song; Han, Weiqi; Wang, Shuo
Abstract: Thalictrum viscosum W.T.Wang & S.H.Wang, 1979 is a flowering plant species in family Ranunculaceae that is endemic to Yunnan province of China. To facilitate genetic study of T. viscosum, we de novo assembled and annotated the complete chloroplast (cp) genome of T. viscosum for the first time. The total length of the cp genome of T. viscosum was 155, 984 bp, with a GC content of 38.4%. The T. viscosum cp genome had a typical quadripartite structure with a large single-copy region of 85, 339 bp, a small single-copy region of 17, 656 bp, and a pair of inverted repeat regions of 26, 495 bp. The cp genome consisted of 133 genes, including 87 protein-coding genes, 38 transfer RNA genes, and eight ribosomal RNA genes. We performed phylogenetic analysis of T. viscosum with the maximum-likelihood phylogenetic tree and indicated that T. viscosum was closely related to T. cirrhosum and T. foeniculaceum.